Psikoedukasi Pemahaman Peran Gender pada Ibu Rumah Tangga di Wilayah Suburban - Izharuddin, Syahid; Wahyuni, Lussy Dwiutami; Suryaratri, Ratna Dyah; Ariyani, Mira; Wijaya, Redo Tridinata; Simanjuntak, Dewi Fransiska (Jendela Akademika, 2025)
Divorce is a significant social issue with significant impacts on individuals' psychological well-being, financial stability, and social dynamics. Key factors contributing to divorce include economic stress, ongoing marital conflict, and the negative impact of spouses' mental and physical health issues. According to the latest data, West Java was recorded as the province with the highest number of divorces in 2024. This community service activity examines the role of gender role perceptions in contributing to domestic conflict. Gender roles, as social constructs that determine expected behaviors and responsibilities of men and women, often contribute to inequalities in access to resources and decision-making power. Comparison of pretest and posttest scores indicates that gender equality education plays a significant role in creating healthier family dynamics and reducing the risk of divorce, particularly in suburban communities. These results highlight the importance of integrating gender equality training into community empowerment programs to address the root causes of domestic conflict.